Quantitative effects of the shale oil revolution - Cristiana Belu Mănescu; Galo Nu\~no (European Central Bank (ECB), 2015)
The aim of this paper is to analyze the impact of the so-called “shale oil revolution”on oil prices and economic growth. We employ a general equilibrium model of the world oil market in which Saudi Arabia is the dominant firm, with the rest of the producers as a competitive fringe. Our results suggest that most of the expected increase in US oil supply due to the shale oil revolution has already been incorporated into oil prices and that it will produce an additional increase of 0.2 percent in the GDP of oil importers in the period 2010-2018. We also employ the model to analyse the collapse in oil prices in the second half of 2014 and conclude that it was mainly due to positive unanticipated supply shocks.
Keywords: Q41; Q47; E17; 330; general equilibrium; Saudi Arabia; shale oil